The Relationship of Parenting Style and the Role of Peers with the Self-Efficacy of Adolescent Victims of Cyberbullying - Rakinaung Natalia; Kerangan Johanis; Palit Fransin Junita (GLOBAL HEALTH SCIENCE GROUP, 2021)
Weak parental control and also the role of peers make cyberbullying incidents in adolescents occur continuously. Cyberbullying has an impact on adolescents physically such as insomnia, loss of appetite and fatigue, psychologically adolescents will often feel depression and anxiety, and psychosocial Adolescents will feel more isolated, social rejection, and sense of being alone. This study aims to determine the relationship between parenting style and the role of peers with the self-efficacy of adolescent victims of cyberbullying in Matani II, Tomohon City. This research is a quantitative study using a cross sectional study design, the instrument of this study using a questionnaire. The respondents are adolescent aged 14 -17 years who are victims of cyberbullying by using non-probability sampling with purposive sampling technique with total 50 respondents. This research uses Spearman's rho statistical test. The result of this study about the relationship between parenting style and the self-efficacy of adolescent victims of cyberbullying and got the r-value = 0.000 ( a = 0.05) and the relationship between the role of peers and the self-efficacy of adolescent victims cyberbullying got the result r-value = 0.001. Based on the result, there is a strong relationship between parenting style of parents and role of peers with the self-efficacy of adolescent victims of cyberbullying in Matani II, Tomohon City.